1999
DOI: 10.1051/aas:1999499
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary synthesis of simple stellar populations

Abstract: Abstract. We construct evolutionary synthesis models for simple stellar populations using the evolutionary tracks from the Padova group (1993, 1994), theoretical colour calibrations from Lejeune et al. (1997Lejeune et al. ( , 1998 and fit functions for stellar atmospheric indices from Worthey et al. (1994).A Monte-Carlo technique allows us to obtain a smooth time evolution of both broad band colours in UBVRIK and a series of stellar absorption features for Single Burst Stellar Populations (SSPs). We present co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
85
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 28 publications
3
85
0
Order By: Relevance
“…This effect is strongest in (V − K) and can amount to more than 1 mag in (V − K) at solar metallicity as seen in Fig. 1, where we plot the (V − K) color evolution for an SSP based on isochrones including the TP-AGB in comparison with an SSP from Kurth et al (1999) based on the Padova stellar evolutionary tracks that did not include the TP-AGB phase. The effect is weaker at lower metallicities and for colors at shorter wavelengths.…”
Section: Input Physics: Padova Isochrones With Tp-agbmentioning
confidence: 95%
See 2 more Smart Citations
“…This effect is strongest in (V − K) and can amount to more than 1 mag in (V − K) at solar metallicity as seen in Fig. 1, where we plot the (V − K) color evolution for an SSP based on isochrones including the TP-AGB in comparison with an SSP from Kurth et al (1999) based on the Padova stellar evolutionary tracks that did not include the TP-AGB phase. The effect is weaker at lower metallicities and for colors at shorter wavelengths.…”
Section: Input Physics: Padova Isochrones With Tp-agbmentioning
confidence: 95%
“…We supplemented these Padova isochrones by low mass stars in the mass range from 0.15−0.45 M from the calculations of Chabrier & Baraffe (1997) that include a new description of the interior of low mass objects and use non-grey atmospheres (see Kurth et al 1999 for details). The Padova group recently added low mass-stars to their isochrones themselves (Girardi et al 2000) but did not compare their low mass stars to those of Chabrier & Baraffe.…”
Section: Input Physics: Padova Isochrones With Tp-agbmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, compared the integrated colours of globular clusters in the Milky Way and M31 with population synthesis models of Bruzual & Charlot (as reported in Leitherer et al 1996), and Kurth, Fritze-von Alvensleben & Fricke (1999), as well as updated versions of Corresponding author: graeme@ucolick.org the Worthey (1994) models. They concluded that an age difference of 4 Gyr or more was needed between metal-rich and metal-poor clusters in order to provide the best model fits to their colours, with the metal-rich clusters being systematically younger.…”
Section: Introductionmentioning
confidence: 99%
“…continue to be improved. Successive generations of modelers have combined the best available knowledge on the ingredients of population synthesis models to predict the appearance of the combined light of generations of stars (Tinsley 1980;Bruzual 1983;Arimoto & Yoshii 1987;Charlot & Bruzual 1991;Bertelli et al 1994;Lançon & Rocca-Volmerange 1996;Fioc & Rocca-Volmerange 1997;Kurth et al 1999;Leitherer et al 1999;Girardi et al 2000). Nevertheless the actual understanding of near-infrared properties has remained a subject of debate, in particular at intermediate ages, between 0.1 and 2-3 Gyr (Girardi & Bertelli 1998;Maraston 1998).…”
Section: Introductionmentioning
confidence: 99%